2021
DOI: 10.1007/s43154-021-00062-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of NASA Human-Robot Interaction in Space

Abstract: Purpose of Review This review provides an overview of the motivation, challenges, state-of-the-art, and recent research for human-robot interaction (HRI) in space. For context, we focus on NASA space missions, use cases, and systems (both flight and research). However, the discussion is broadly applicable to all activities in space that require or make use of human-robot teams. Recent Findings To date, HRI in space has largely been limited to remote interaction between humans on Earth and robots in space. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…In 2021 the requirement for maintenance of personal space of both humans and human-like avatars has been modelled [122] and reported that discomfort-bydistance functions for both humans and avatars were closely aligned in a power relationship. This reinforces the notion that humans need personal space not just from other humans, but may also need space from human-like objects which could become important for future design of humanoid robots [123][124][125][126].…”
Section: Emergency Evacuation Protocol and Processes Clinical Waste M...supporting
confidence: 68%
“…In 2021 the requirement for maintenance of personal space of both humans and human-like avatars has been modelled [122] and reported that discomfort-bydistance functions for both humans and avatars were closely aligned in a power relationship. This reinforces the notion that humans need personal space not just from other humans, but may also need space from human-like objects which could become important for future design of humanoid robots [123][124][125][126].…”
Section: Emergency Evacuation Protocol and Processes Clinical Waste M...supporting
confidence: 68%
“…Moreover, agents must be competent and empowered to make decisions when needed, without having to wait for instructions from humans, especially in extreme environments where humans must adapt to particular conditions (Hambuchen et al, 2021 ), and resources are scarce. System resilience is also of high importance as the consequences of failure, on either side (human or agent) could be catastrophic.…”
Section: Human-ai Multi-team Systemsmentioning
confidence: 99%
“…Human localization is an active research topic with many applications, from the accurate determination of human position in teams of humans and mobile robots to the study of human biomechanics. The variety of fields implementing human–robot teams includes agriculture [ 1 ], mining [ 2 ], search-and-rescue [ 3 ], and exploration [ 4 ]. Each sector has its own requirements for safe and effective human–robot teams due to the different environments and levels of human involvement.…”
Section: Introductionmentioning
confidence: 99%